Assessment of hegemonic and peripheral healthcare systems: a methodological proposal (Sustainability in Debate, 2025)
Applied research conducted with some traditional populations has served as the methodological foundation for the social interaction system (SIS) model, which seeks to contrast the hegemonic market system with peripheral socioenvironmental systems. The aim is to check whether the methodology of this model can be extrapolated to the healthcare system. The theoretical framework on peripheralmodernity, hegemony, and subalternity serves as a foundation for analysing the historical contexts in which alternative healthcare experiences take place. Arguments from authors who question the hegemonic healthcare system help explore viable alternatives. This raises the question of whether the SIS model can effectively interpret the limitations and potentialities of different health systems,particularly analysing whether the hegemonic and alternative systems can coexist as hybrid systems and what essential conditions underpin such coexistence. Moreover, some of the key limitations and obstacles are discussed, and suggestions are given to enhance communication among different healthcare systems.